Successful banking in an enlarged EU - Erich Hampel (EIB Papers, 2002)
From the single-tiered banking system of the late 1980s, still ruled by the communist party, Eastern Europes financial system has evolved towards one which EU countries have long been accustomed to. Central and Eastern European Countries (CEEC) are now on the brink of EU membership, and accession to the European Union requires the implementation of the acquis communautaire, the set of laws that underpin the common market. As a result of adapting to the acquis, the CEEC financial systems have already been transformed to such an extent that the supervisory and legal framework has more or less reached EU standards.
Keywords: 330; Bank; EU-Erweiterung; Osteuropa